Structural design of a positioning spherical parallel manipulator to be utilized in brain biopsy. Issue 5 (12th June 2019) - Gezgin, Erkin; Özbek, Seda; Güzin, Didem; Ağbaş, Ozan Emre; Gezer, Emin Burak
Abstract: Background: During the last decades, there has been a great increase in the usage of robotic systems during surgeries in order to reach increased operational precision, reduced operation times, enhanced recovery periods, low infection risks, and limited scar formations for aesthetic reasons. In light of this, the current study focuses on the field of robotic surgery by introducing the kinematic structure of the precise robotic positioning manipulator for brain biopsy. Methodology: Throughout the study, two degrees of freedom spherical parallel robot manipulator was proposed in order to position brain biopsy needle precisely during the brain biopsy operation on the target workspace. Results: Direct and inverse kinematics of the manipulator were carried out parametrically by using quaternion algebra. The prototype of the manipulator was manufactured by rapid prototyping for hardware verification. Conclusions: Hardware verification of the manufactured prototype was completed distinctly by using motion capture cameras and manufactured mock‐up setup that mimics tumour locations inside the brain. Successful verification results in terms of precision were achieved.